Removal of dye by adsorption of eggshell powder - Chin, Chiek Ee, 1990-, author; Norzita Ngadi, supervisor; Fakulti Kejuruteraan Kimia (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2013)
Project Paper Sarjana Muda Kejuruteraan (Kimia) - Universiti Teknologi Malaysia, 2013